KELUARGA KRISTIANI DAN PENDIDIKAN ANAK DALAM TERANG GRAVISSIMUM EDUCATIONIS ARTIKEL 3 - Agustinus Supriyadi (Bahasa Indonesia, 2018)
Family is a community first formed by husband and wife, then evolved towards communion parents with children. Christian families are called to take part actively and responsibly in the Church’s mission in a way that is original and distinctive through his presence and, as a community of life and affection to serve the Church and society. Children’s education is born from the goal of a marriage which is happiness conjugal and family in all aspects of life as well as the birth of a child and the child's faith education. The main task of parents as educator lies in the love between children and parents themselves. Parents are the first and primary educators. As the first and primary educators, parents reveal a fundamental authority to educate their children. Education is basically focused on personal development as complete physical-spiritual man, both as personal and social beings, within the framework of his last life goals. Community and Church help parents to remain in their position and role as the primary educator and the first for their children.